2022
DOI: 10.1007/s40120-022-00356-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Neuromyelitis Optica Spectrum Disorder on Quality of Life from the Patients’ Perspective: An Observational Cross-Sectional Study

Abstract: Introduction Neuromyelitis optica spectrum disorder (NMOSD) is associated with a reduced health-related quality of life (HRQoL). The purpose of this study was to describe the impact of NMOSD on HRQoL from the patients’ perspective and its relationship with other disease factors. Methods An observational, cross-sectional study was conducted at 13 neuroimmunology clinics in Spain. Patients with NMOSD diagnosis (2015 Wingerchuk criteria) were included. The 29-item Multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Our study is consistent with others who have identified a high unemployment rate and limited full‐time employment among study participants with NMOSD. Prior work on NMOSD found 11% to 35% of participants from the United States, Spain, and United Kingdom were employed 12–14 . However, these prior studies did not specifically aim to characterize employment of NMOSD patients and had study populations that were about 6 years older on average.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is consistent with others who have identified a high unemployment rate and limited full‐time employment among study participants with NMOSD. Prior work on NMOSD found 11% to 35% of participants from the United States, Spain, and United Kingdom were employed 12–14 . However, these prior studies did not specifically aim to characterize employment of NMOSD patients and had study populations that were about 6 years older on average.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work on NMOSD found 11% to 35% of participants from the United States, Spain, and United Kingdom were employed. 12 , 13 , 14 However, these prior studies did not specifically aim to characterize employment of NMOSD patients and had study populations that were about 6 years older on average. This inevitably increased the number of retired participants included.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no clear consensus on how relapse severity is defined in clinical practice and current mildness does not necessary reflect the same in subsequent relapses, the prevention of all relapses being the therapeutic goal regardless of their severity ( 6 , 7 , 38 , 39 ). In fact, patients describe disease stability as the absence of any relapse, since they focus on the impact relapses have on daily life and wellbeing ( 40 , 41 ). Thus, the relapsing nature of the disease together with the importance of a patient-centered approach with shared decision-making should lead to a shift in the treatment paradigm to early use of high-efficacy therapies when treating this condition, as it is evolving in the MS field ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Depression and anxiety are common among individuals with NMOSD, with 30% to 50% endorsing clinically significant depressive symptoms [7][8][9][10] and 33% endorsing anxiety [11]. NMOSD patients are twice as likely to experience Major Depressive Disorder and high suicidal risk, as compared with patients with Multiple Sclerosis [9].…”
Section: Introductionmentioning
confidence: 99%